Local regulatory governance in the Philippines focus on Quezon City - Legaspi, Perla E. (2003)
The 1987 Constitution and the Local Government Code of 1991 have transferred regulatory powers of national government agencies to the local governments, for a more responsive and accountable local government. This study traces developments of this change, through a discussion of the present regulatory framework at the local level, the local government role in facilitating economic development, and the issues and concerns in regulating business or economic activities in the local area. The research cites Quezon City, a premier local government authority in the Metropolitan Manila area: examining its regulatory system and focusing on its business licensing system. It also looks into the issues, problems, and concerns in regulating the operations of business establishments and enterprises in the city. Lastly, the study showcases changes and reforms introduced, as well as, the effects of the regulatory system on the promotion of business or economic activities in the city.
Keywords: Barangay micro business enterprises; Business licensing systems -- Quezon City; Business licenses -- Quezon City; Local regulatory governance